Management and the arts - Byrnes, William J. (Burlington, MA : Focal Press, 2014)
"The fifth edition of Management and the Arts provides you with theory and practical applications from all arts management perspectives including planning, marketing, finance, economics, organization, staffing, and group dynamics. Regardless of whether you are a manager in a theatre, museum, dance company, or opera, you will gain useful insights into strategic planning, organization, and integrated management theories. Case studies, statistics, and real-world examples will allow you get a handle on all aspects of arts managements, from budgeting and fundraising, to e-marketing and social networking, to working effectively with boards and staff members. Revised to reflect the latest thinking and trends in managing organizations and people, this fifth edition features class-tested questions in each chapter, which help you to integrate the material and develop ideas about how the situations and problems could have been handled. Case studies focus on the challenges facing managers and organizations every day, and "In the News" quotes give you real-world examples of principles and theories. NEW TO THIS EDITION: - Sections on grant research and writing, social networking, and fundraising - Resources for developing career skills, graduate, and postgraduate training opportunities, and information on professional organizations and conferences - Expanded material on volunteers in the arts, more coverage of international perspectives, and more information on integrated software solutions and on budgeting - A companion website at www.managementandthearts.com with a sample syllabus, additional project assignments, suggested resources, and chapter-by-chapter PowerPoint slides"--Provided by publisher.
boek